THE CHINESE ORCHESTRA CULTURAL ECOSYSTEM IN MALAYSIA: HYBRIDISATION, RESILIENCE AND PREVALENCE (Journal of Creative Industry and Sustainable Culture, 2023)
While the Chinese orchestra is a relatively modern formation, its Chinese folk music predecessorsand their relationship with their host environmenthas a long, traceable history. Traditionally, Chinese music has nurtured a close identification with natural phenomena, from the use of natural resources in the construction of instruments, classified as the bayin,to the portrayal of imageries of the soundscapes of nature with extended performance techniques. Along with globalisation trends, Chinese folk music traditions have since undergone a series of hybridisation and transformation processes that transposed its focus from the natural/individual into the social/communal, mimicking the Western symphony orchestral model, a process that fostered the constant modification, repurposing, and commodification of its instruments and practices. Applying Titon’s concept of ecomusicology as the theoretical framework, the present study explores the resilience and adaptive management of the Chinese orchestra since the inception of its model 100 years ago, particularly in the context of the Chinese diaspora in Malaysia. How does Chinese music in a diasporic location retain and adapt its historical aesthetics, after undergoing politically induced transformations, pressures of modernisation and desires of assimilation into the local community? This study proposes a participant observation to reassess the current state of the Chinese orchestra in Malaysia, while providing an update on the limited existing literature on the topic through the perspective of cultural ecosystems. With tensions of modernising according to social trends and additional challenges posed by social configurations, repositioning the study of Malaysian Chinese Orchestras as ecosystem would help to devise new strategies to sustain the model in the future, while keeping its identity as a ‘tradition’ that is experiencing constant evolution.